VILLAGE BRANDING BASED ON DEVELOPMENT OF MSMEs - Mohammad Ikhsan Kurnia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Village branding based on the development of Micro, Small and Medium Enterprises (MSMEs) is an innovative approach that aims to increase the economic potential and welfare of village communities. Village branding integrated with MSME development can create an environment that supports local business growth, increases market access, and optimizes the use of local resources. Apart from that, village branding also contributes to increasing community skills and knowledge, increasing their participation in decision-making processes, and improving basic infrastructure that supports economic sustainability. This research aims to get an overview of village branding based on MSME development in Indonesia which has been studied by researchers based on community service activities carried out by university personnel. The approach used is a qualitative approach with a literature review method based on data obtained from the Garuda Platform. This research succeeded in reviewing 9 literature documents regarding MSME-based village branding. The results of the literature review identified problems faced by MSMEs in Indonesia, including lack of literacy about branding, digital marketing, operational management, financial management and use of technology. Keywords: MSMEs, Village, Brand, Literature Review.